Liquidity as Mediation of DER and DAR on NPM in LQ45 for the 2019-2023 Period - Ramadhani, Fitria; Firdaus, Firdaus; Nurhayati, Nurhayati; Purwanto, Dedik (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The aim of this research is to study how the liquidity ratio functions as a mediating variable in the relationship between Debt to Equity Ratio (DER) and debt to asset ratio (DAR) to net profit margin (NPM) in LQ45 companies listed on the IDX during the 2019-2023. Methodology: The quantitative method used in this research uses data from company financial reports for five years. To select samples, purposive sampling technique was used. The influence of direct and indirect variables is evaluated through data analysis using Modeling Equation Structural-Partial Least Squares (SEM-PLS). Results: Research shows that DER has a positive and significant influence on NPM and liquidity ratios, while DAR has a negative influence on both. The liquidity ratio functions as a positive mediation between DER and NPM, but only affects NPM directly. Conclusions: The research findings indicate that Return on Equity (ROE) significantly and positively influences the prediction of financial distress in Islamic banking in Indonesia. Conversely, Capital to Total Deposit (CTD) shows a significant negative effect, suggesting that a higher CTD ratio reduces the likelihood of financial distress. Meanwhile, the Loan to Total Asset (LTA) ratio, although showing some influence, does not have a statistically significant effect on predicting financial distress. Limitations: This study has a limited sample size and observation period. Therefore, the findings do not fully reflect conditions or trends not included in the sample. Contribution: This research provides opportunities for further studies with other mediating variables to understand more deeply the financial dynamics of companies in the Indonesian capital market and provide an important contribution to capital structure management in an effort to increase company profitability and liquidity.